TINJAUAN HUKUM INTERNASIONAL TERHADAP UJICOBA NUKLIR KOREA UTARA DAN KAITANNYA DENGAN PERDAMAIAN DAN STABILITAS KEAMANAN GLOBAL - Chrisyela Sinaga; Jelly Leviza; Sutiarnoto Sutiarnoto (Journal of USU International Law, 2013)
ABSTRACT This study aims to determine the regulation of nuclear in international law perspection, international legal regulation in maintaining peace and stability of global security and shape the rules issued by the United Nations in the form of UN Security Council Resolution related to North Korea's nuclear test on 12 February 2013 in order to maintain peace and stability of the global security . The method used is the normative legal research with specification of descriptive research. The results are presented systematically through data collection is done by seeking information through library or secondary data including primary legal materials, secondary and tertiary-related issues. The results showed that the rule of international law that regulates nuclear contained in the UN Charter, UN General Assembly Resolution, UN Security Council Resolution, and the Statute of the IAEA. Setting of international law in maintaining global peace and security stability seen from the formation of the United Nations whose purpose is to maintain international peace and security. The rules issued by the United Nations in the form of UN Security Council Resolution related to North Korea's nuclear test on 12 February 2013 were the United Nations Security Council Resolution No. 2094 which provides for sanctions against North Korea in the form of an order to North Korea to abandon all nuclear weapons programs, enforcement of sanctions new finance to block financial transactions that support North Korea's illegal activities, inspection of suspicious cargo and denial of access to ports and shipping cost related to North Korea in accordance with the law and allow stronger enforcement of the sanctions that have been imposed by the UN Member States. Keywords: Nuclear Tests, Nuclear North Korea, Peace and Global Security